Outcomes for Dostarlimab and Real-World Treatments in Post-platinum Patients With Advanced/Recurrent Endometrial Cancer: The GARNET Trial Versus a US Electronic Health Record-Based External Control Arm - Scott Goulden; Qin Shen; Robert L. Coleman; Cara Mathews; Matthias Hunger; Ankit Pahwa; Rene Schade (Journal of Health Economics and Outcomes Research)
**Background:** Patients with advanced or recurrent endometrial cancer (EC) have limited treatment options following platinum-based chemotherapy and poor prognosis. The single-arm, Phase I GARNET trial (NCT02715284) previously reported dostarlimab efficacy in mismatch repair–deficient/microsatellite instability–high advanced or recurrent EC.